Віддалені результати хірургічного лікування раку щитоподібної залози - Ларін, О. С. (Clinical Endocrinology and Endocrine Surgery, 2008)
In the article the 5 and 10 years results of surgical treatment of 1366 (76%) from 1797 primary cases of thyroid cancer have been analyzed. All patients were operated within 1996-2006 years in Ukrainian scientific and practical center of endocrine surgery. Indices of survival, cancer specific mortality, rate of relapses and distant metastases were calculated separately for each morphologic form of thyroid carcinoma and for each clinical stage of patients. Despite good overall 10 years survival (92%) contributed by favorable out comes of the most common papillary and follicular thyroid carcinoma, corresponding indices for less common (4% of all cases) medullary carcinoma are much worser (80% and 67% at 5 and 10 years after operation). Poor differentiated and particularly undifferentiated (anaplastic) thyroid cancer demonstrated extremely unfavorable prognosis with no survival beyond 1 year after operation for anaplastic tumor. These both morphologic forms comprise 1.5% of all cases of thyroid cancer whereas papillary and follicular carcinomas comprise 85% and 9% correspondingly.